Future climate risks from stress, insects and fire across US forests. (11th May 2022) - Anderegg, William R. L.; Chegwidden, Oriana S.; Badgley, Grayson; Trugman, Anna T.; Cullenward, Danny; Abatzoglou, John T.; Hicke, Jeffrey A.; Freeman, Jeremy; Hamman, Joseph J.
Abstract: Forests are currently a substantial carbon sink globally. Many climate change mitigation strategies leverage forest preservation and expansion, but rely on forests storing carbon for decades to centuries. Yet climate‐driven disturbances pose critical risks to the long‐term stability of forest carbon. We quantify the climate drivers that influence wildfire and climate stress‐driven tree mortality, including a separate insect‐driven tree mortality, for the contiguous United States for current (1984–2018) and project these future disturbance risks over the 21st century. We find that current risks are widespread and projected to increase across different emissions scenarios by a factor of >4 for fire and >1.3 for climate‐stress mortality. These forest disturbance risks highlight pervasive climate‐sensitive disturbance impacts on US forests and raise questions about the risk management approach taken by forest carbon offset policies. Our results provide US‐wide risk maps of key climate‐sensitive disturbances for improving carbon cycle modeling, conservation and climate policy. Abstract : We quantify the climate risks to US forests of fire, climate stress and insect‐driven disturbance. We find widespread risks that increase substantially in future climate scenarios.